PENATAAN PERMUKIMAN KUMUH TEPIAN SUNGAI, KASUS KAWASAN KELURAHAN BAAMANG HILIR TEPIAN SUNGAI MENTAYA, KECAMATAN BAAMANG, SAMPIT KABUPATEN KOTAWARINGIN TIMUR, KALIMANTAN TENGAH - Ribka Yunithea (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2023)
Kotawaringin Timur is known as a city with life related to rivers, especially the Mentaya River which is the center of life for the people of the city itself. Baamang Hilir is one of the villages classified as slums and densely packed in Baamang, East Kotawaringin. The lives of the people in Baamang Hilir depend on the area where they live, which is not balanced with the level of awareness and concern to care for and maintain the sustainability of the residential environment. The purpose of this study is to determine the characteristics of the location in terms of achievement and proximity, policies related to the location of the object of study, knowing the level of slums and the concept of structuring, as well as the concept of structuring in other locations with similar location characteristics. The analysis is divided into 4 parts, location and site analysis, policy analysis, slum characteristics analysis, and best practices analysis. Based on the results of the analysis, it was found that the location of the study object was classified as a medium to high slum. Priority aspects in structuring are aspects of the physical condition of buildings and infrastructure. So it is proposed to arrange houses on water, houses above ground, repair of clean waterways, sanitation of MCK, roads, and the creation of TPS. With an arrangement that focuses on these two aspects, it will affect the improvement of two other aspects, namely the social aspect and the economic aspect. In addition, the proposed structuring concept retains cultural and historical elements at the location of the object of study. Keywords: areas; arrangement; riverbanks; settlements; slums Abstrak Kabupaten Kotawaringin Timur dikenal sebagai kota dengan kehidupan yang berkaitan dengan sungai, terutama Sungai Mentaya yang menjadi pusat kehidupan bagi masyarakat kota itu sendiri. Kelurahan Baamang Hilir merupakan kelurahan yang tergolong sebagai kawasan permukiman kumuh dan padat di Kecamatan Baamang, Kabupaten Kotawaringin Timur. Kehidupan masyarakat yang berada di Kelurahan Baamang Hilir bergantung pada wilayah tempat tinggal, namun kurang diimbangi dengan tingkat kesadaran dan kepedulian untuk merawat serta menjaga kelestarian lingkungan permukiman. Tujuan dari penelitian ini untuk mengetahui karakteristik lokasi dari segi pencapaian dan kedekatan, kebijakan terkait lokasi objek studi, mengetahui tingkat kekumuhan dan konsep penataan, serta konsep penataan di lokasi lain dengan karakteristik lokasi yang serupa. Analisis dibagi menjadi 4 bagian yaitu analisis lokasi dan tapak, analisis kebijakan, analisis karakteristik permukiman kumuh, dan analisis best practices. Berdasarkan hasil analisis tersebut didapatkan hasil bahwa lokasi objek studi tergolong dalam kumuh sedang hingga tinggi. Aspek prioritas dalam penataan berupa aspek kondisi fisik bangunan dan sarana prasarana. Sehingga diusulkan penataan rumah di atas air, rumah di atas tanah, perbaikan jalur air bersih, sanitasi MCK, jalan, dan pembuatan TPS. Dengan adanya penataan yang berfokus pada kedua aspek tersebut, maka akan mempengaruhi peningkatan dua aspek lainnya yaitu aspek sosial dan aspek ekonomi. Selain itu konsep penataan yang diusulkan tetap mempertahankan unsur budaya dan sejarah di lokasi objek studi.